1993
DOI: 10.1002/prac.19933350112
|View full text |Cite
|
Sign up to set email alerts
|

Herstellung von hydrolysestabilen Ammoniumsalzen sulfonierter Phosphite und deren Einsatz als Cokatalysatoren in der rhodiumkatalysierten Hydroformylierung

Abstract: Hydrolytic Stable Ammonium Salts of Sulfonated Organic Phosphites and their Use as Cocatalysts in the Rhodium‐catalyzed Hydroformylation of Olefins Ammonium salts of sulfonated organic phosphites, which are resistant to hydrolysis, have been prepared by transesterification of triphenylphosphite with mono‐ammonium salt of p‐hydroxyphenylsulfonic acid in yields between 66 and 76%. A mixture containing triisooctylammonium salts of sulfonated triphenylphosphite [TPPp‐SO3HN(i‐octyl)3] was submitted to a test for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The hydrophilic phosphite L c was made according to the route shown in Scheme 1. Treatment of the rigorously dried trioctylammonium salt of the commercially available calix [4]arene tetrasulfonic acid with P(NMe 2 ) 3 in CH 2 Cl 2 followed by bubbling gaseous NHMe 2 through the solution gave a white precipitate which was assigned to the six-coordinate phosphorus species 1 ( 31 P NMR in D 2 O, d À124.5 1 J(PH) 730 Hz) from the close similarity of its 31 P NMR data to the analogous nonsulfonated species. 6 Solid 1 could be stored for weeks without change but in water, 1 converted over a period of 1 hour to phosphite L c as shown by its characteristic 31 P chemical shift of 113.5 ppm (cf.…”
Section: Ligand Synthesis and Stabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The hydrophilic phosphite L c was made according to the route shown in Scheme 1. Treatment of the rigorously dried trioctylammonium salt of the commercially available calix [4]arene tetrasulfonic acid with P(NMe 2 ) 3 in CH 2 Cl 2 followed by bubbling gaseous NHMe 2 through the solution gave a white precipitate which was assigned to the six-coordinate phosphorus species 1 ( 31 P NMR in D 2 O, d À124.5 1 J(PH) 730 Hz) from the close similarity of its 31 P NMR data to the analogous nonsulfonated species. 6 Solid 1 could be stored for weeks without change but in water, 1 converted over a period of 1 hour to phosphite L c as shown by its characteristic 31 P chemical shift of 113.5 ppm (cf.…”
Section: Ligand Synthesis and Stabilitymentioning
confidence: 99%
“…1,2 Triaryl phosphites are excellent ancillary ligands for Rh-catalysed hydroformylation 3 but the kinetic instability of P-OR bonds to hydrolysis would appear to preclude making water-soluble sulfonated phosphites with any useful lifetime. Indeed Fell et al 4 showed that a mixture of sulfonated triphenylphosphites (TPOPS) (as tri-isooctylammonium salts) completely decompose in aqueous acetone after 24 h and Karakhanov et al 5 also reported that a polyether phosphite rapidly decomposed in the presence of water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16] A cationic phosphinite obtained by reaction of trimethyloxonium tetrafluoroborate with an aminophosphinite (Scheme 3) was prepared in situ and directly reacted with rhodium in a reaction of catalytic asymmetric hydrogenation. [21] The only cationic phosphite described in the literature was obtained by reaction of methyl iodide with the tris-[3-(N,N-dimethylamino)-phenyl] phosphite to form the ammonium compound (Scheme 4). [25] This compound was not characterized further than the determination of its melting point.…”
Section: Synthesis Of Ionic Aryl Phosphitesmentioning
confidence: 99%